THE CORRELATION BETWEEN SPEAKING SKILL AND READING COMPREHENSION (A CASE STUDY ON THE THIRD SEMESTER OF ENGLISH STUDY PROGRAMAT ISLAMIC UNIVERSITY OFINDRAGIRI TEMBILAHAN) - Maizarah Maizarah; Sri Erma Purwanti (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Speaking is a skill to produce sequences of words that exist at the meaning while reading means a skill to get meaning from the written words. Vocabulary is the key in which these two skills relate to each other. The purpose of this study was to investigate the correlation between speaking skill and reading comprehension of the third semester English students at Islamic University of Indargiri. The sample of this study was 20 students. The research method used in this study was a correlational study. Researchers gave the test of speaking skills and reading comprehension to collect data. After the data has been collected, it was found that the average of the students’ speaking skills was categorized as Good because 70,8 in range 66-79 and the students’ reading comprehension was categorized as Good to Excellentbecause 78,7 in range 76-100. Based on those findings, researchers analyzed the students’ speaking skill and their reading comprehension by using Pearson r formula, with the result is 0,691. Based on the coefficient correlation, 0,691 was interpreted as Moderate Correlation. It means there is a significant correlation between students’ speaking skill and their reading comprehension.